Disodium cromoglycate inhibits asthma-like features induced by sphingosine-1-phosphate. (November 2016) - Roviezzo, Fiorentina; Sorrentino, Rosalinda; Iacono, Valentina Mattera; Brancaleone, Vincenzo; Terlizzi, Michela; Riemma, Maria Antonietta; Bertolino, Antonio; Rossi, Antonietta; Matteis, Maria; Spaziano, Giuseppe; Pinto, Aldo; D'Agostino, Bruno; et al.
Graphical abstract: Abstract: Compelling evidence suggests the involvement of sphingosine-1-phosphate (S1P) in the pathogenesis of asthma. The systemic administration of S1P causes asthma like features in the mouse involving mast cells. In this study we investigated whether disodium cromoglycate (DSCG), administered as a preventative treatment as in human therapy, could affect S1P effects on airways. BALB/c mice, treated with DSCG, received subcutaneous administration of S1P. Bronchi and pulmonary tissues were collected and functional, molecular and cellular studies were performed. DSCG inhibited S1P-induced airway hyper-reactivity as well as pulmonary inflammation. DSCG decreased the recruitment of solely mast cells and B cells in the lung. IgE serum levels, prostaglandin D2, mucus production and IL-13 were also reduced when mice were pretreated with DSCG. S1P induced pulmonary expression of CD23 on T and B cells, that was reversed by DSCG. Conversely, S1P failed to upregulate CD23 in mast cell-deficient Kit W−sh/W−sh mice. In conclusion we have shown that DSCG inhibits S1P-induced asthma like features in the mouse. This beneficial effect is due to a regulatory action on mast cell activity, and in turn to an inhibition of IgE-dependent T and B cells responses.